2011
DOI: 10.1016/j.jcv.2011.07.016
|View full text |Cite
|
Sign up to set email alerts
|

Keratoconjunctivitis sicca of human T cell lymphotropic virus type 1 (HTLV-1) infected individuals is associated with high levels of HTLV-1 proviral load

Abstract: HTLV-1 proviral loads are higher in patients with KCS and may represent a relevant biological marker of disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 36 publications
1
14
0
Order By: Relevance
“…In the last few years, numerous studies have demonstrated a clear association between high PVL and development of HAM/TSP and of other inflammatory conditions such as infective dermatitis and keratoconjunctivitis sicca. Patients with these conditions have a PVL consistently higher than asymptomatic carriers [22, 24, 30]. Recently, our group suggested a cutoff of 5% infected cells as best the value to differentiate HAM/TSP patients from asymptomatic individuals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the last few years, numerous studies have demonstrated a clear association between high PVL and development of HAM/TSP and of other inflammatory conditions such as infective dermatitis and keratoconjunctivitis sicca. Patients with these conditions have a PVL consistently higher than asymptomatic carriers [22, 24, 30]. Recently, our group suggested a cutoff of 5% infected cells as best the value to differentiate HAM/TSP patients from asymptomatic individuals.…”
Section: Discussionmentioning
confidence: 99%
“…HTLV-1 PVL is considered low if the proportion of infected PBMCs is lower than 1%, and high if greater than 5% [20]. High PVLs are commonly found in individuals with HAM/TSP [21, 22], infective dermatitis [23] and Keratoconjunctivitis sicca [24]. However, in some cases, asymptomatic individuals may have high PVLs and exhibit an exacerbated inflammatory response [14, 22].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, compelling evidence indicates that patients with other HTLV-1-associated inflammatory conditions, such as infective dermatitis [12] or keratoconjunctivitis sicca [13], display significantly higher levels of proviral load compared to asymptomatic carriers.…”
mentioning
confidence: 99%
“…Clinically, overlap of HU and HAM is seen in less than 15% of cases (Nakao et al, 2018). KCS and IK, which are partially related to inflammation, are more frequent among HAM patients (Merle et al, 2001;Pinheiro et al, 2006;Castro-Lima Vargens et al, 2011).…”
Section: Overlap Syndromementioning
confidence: 98%